Part I: Synthesis of Quinolones for Inhibition of the Β-barrel Assembly Machine in Gram Negative Bacteria; Part II: Synthesis of Azo Dye Sensors for Detection of Metal Ions in Aqueous Environments - (:unkn) unknown (My University, 2022)
Part I: Antibiotic resistance in Gram-negative bacteria is a growing cause of concern worldwide. Thousands of people die from antibiotic resistant bacteria every year. The β-Barrel Assembly Machine (BAM) in Gram-negative bacteria plays a role in antibiotic resistance as its porin, BamA, can regulate which molecules enter the cell, meaning it can prevent antibiotics from entering the bacterial cell. BamA exists in an open and closed form and is only selective in its closed form. BamA opens and closes through the H-bonding of two intramolecular β-strands. It is theorized that the creation of a β-sheet mimetic, based on work done by James Nowick, would be able to H-bond with one of the β-strands involved in closing BamA, therefore locking it in the open conformation and allowing antibiotics into the cell, thus rejuvenating effectiveness of current antibiotics. Part II: There are metals present in all drinking water, most of which are of minimal health concern. However, across the world there are many instances of harmful metals being found in drinking water. Flint, Michigan is one of these places: their recent lead crisis was only one of many. This is a problem worldwide, and there are currently no regenerable, real-time, and/or consumer-friendly methods of testing drinking water. As such, there is a need for a device that can detect and report small amounts of toxic metals in drinking water in real-time. No device like this currently exists on the market. Azo-dyes function as wonderful metal sensors as evidenced by the Schwabacher group’s previous small metal sensing project. Using this previous project as a general framework, multiple families of azo dyes were designed to meet the goal of detecting low ppb heavy metals in drinking water. These sensors have been tested for their ability to detect lead in aqueous solution as free dyes and have shown a lot of promise in preliminary testing. These sensors are able to enter the next stage of development which is placement onto a polymer and further testing.
Keywords: Azo Dyes; Pb; Quinolones; Sensors; Synthesis